Large cardamom (Amomum subulatum Roxb.) - a review - CHATTERJEE, R NAIDU, C K GEORGE, Y S RAO, ANAND KUMAR, SUJATHA (Journal of Spices and Aromatic Crops, 1993)
Large cardamom (Amomum subulatum) is the most important cash crop of Sikkim and also in parts of North Eastern States and West Bengal in India. The information available on various aspects of the crop viz., improvement, management, pests and diseases and end products are discussed in the review.